2005
DOI: 10.1080/j.1440-1614.2005.01540.x
|View full text |Cite
|
Sign up to set email alerts
|

Accommodation History and Continuity of Care in Patients with Psychosis

Abstract: A history of homelessness is common in patients with psychosis using inner urban mental health services and is associated with poorer engagement with psychiatric services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…[109] The relevance of socioeconomic context was later highlighted in the management of specific health problems including diabetes, [32, 69, 110] rheumatoid arthritis, [61, 63] and psychosis. [62] The specific socioeconomic context of vulnerable housing is a particular challenge: ‘Lack of stable housing can affect a patient’s ability to store and take medications, to care for wounds properly, and to abstain from or limit physical activity during recuperation.’ [68] It was said that acknowledging patients’ socioeconomic contexts could enable improved treatment planning [11, 58, 59, 64, 66] and shared decision-making. [16, 58, 60] It could also improve the effectiveness [65] and outcomes of healthcare, [67] while reducing costs [38] and improving patient satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…[109] The relevance of socioeconomic context was later highlighted in the management of specific health problems including diabetes, [32, 69, 110] rheumatoid arthritis, [61, 63] and psychosis. [62] The specific socioeconomic context of vulnerable housing is a particular challenge: ‘Lack of stable housing can affect a patient’s ability to store and take medications, to care for wounds properly, and to abstain from or limit physical activity during recuperation.’ [68] It was said that acknowledging patients’ socioeconomic contexts could enable improved treatment planning [11, 58, 59, 64, 66] and shared decision-making. [16, 58, 60] It could also improve the effectiveness [65] and outcomes of healthcare, [67] while reducing costs [38] and improving patient satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…Periods of homelessness are common in patients attending community clinics. 18 The capacity to access and work with homeless people may be required for many urban mental health services, practices which may be measured using these PIs.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that men with a psychosis, who experienced homelessness in the previous year, had a mean of 4.1 accommodation settings as compared with 1.8 in those who had not experienced homelessness (Holmes et al . 2005b).…”
Section: Methodsmentioning
confidence: 99%
“…A minority of homeless people with a psychosis remain so long term. In Melbourne, Australia, 13% of homeless men engaged by outreach mental health service had been homeless for more than 12 months (Holmes et al . 2005b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation